INTERAKSI SOSIAL PADA MAHASISWA PESERTA MABINMABA 2017 - Ninawati Lihardja; Monika Monika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2018)
There are many interactions among individuals in society. This research was attempted to describe the patterns of interaction among the “Mabinmaba” student. These patterns of interactions based on friendship, study, personal, and hobby of the students. The participant of this research consist of 120 students, they were separate in 4 groups. They were the student of the Faculty of Psychology. Purposive technique samling used in this research. The result of this research: there are qliques in these 4 groups. The networks based on pesonal issue had less in qlique liaison than the other networks.Ada banyak interaksi antar individu dalam masyarakat. Penelitian ini berusaha menggambarkan pola interaksiantara siswa